A Floristic Inventory in the Banni Region of Bhuj Taluka, Kachchh District, Gujarat (India) - Patel, Yatin; Joshi, P. N. (Indian Forester, 2011)
Ecological and ethnobotanical study in and around the Banni areas,Kachchh district, Gujarat state (India) during 2008-2009, able to list a total 192 plant species. In which,147 species were dicots and the rest (45) were monocots, belonging to 50 families under 142 genera. The species richness and diversity of BR was 192 species which formed 27.43% of the species. The predominant families were Poaceae (34) followed by Astraceae (10), Amaranthaceae (9), Cucurbitaceae (8), Euphorbiaceae (8) and Solanaceae (7). As per IUCN/WCMC categories (1994), two threatened plant species- Ammannia desertorum Blatt. & Hall. and Citrullus colocynthis (L.) Soland., were recorded from seven localities. The study also provide an overview of Medicnal Plants (MPs) with description of medicinal value of 14 plants.